Hubungan Karakteristik, Ketersediaan Fasilitas dan Pengawasan dengan Tindakan Tidak Aman pada Petugas Penanganan Prasarana dan Sarana Umum di Jakarta Timur - NOVIANUS, CORNELIS (ARKESMAS [Arsip Kesehatan Masyarakat], 2019)
ABSTRACT Every job has risks and hazards related to the work performed. The worker for Handling Public Infrastructure and Facilities (PPSU) as the officer in charge of cleaning public facilities in east Jakarta is not immune from risks and dangers when carrying out their duties. Some of the dangers that may occur include the presence of biological, physical, and chemical hazards that can make injuries and illness from occupational diseases. Independent variables of this study are worker characteristics (age, years of service, and education, knowledge, attitudes), facilities availability, and supervision, and the dependent variable is PPSU's unsafe action. The purpose of the study was to relationship characteristics, facilities availability and supervision with unsafe action at PPSU. The study design was cross sectional. The research sample was all PPSU workers in X Village east Jakarta, which were 64 people. Data analysis using univariate and bivariate. The results of the study were mostly unsafe action from PPSU were not risky (57.8%), proportion of old age (50.0%), work period was mostly> 3 years (79.7%), the education of officers was high (78.1%), officer knowledge is also high (71.9%), positive officer attitudes (56.2%), most officers state that the facilities availability are complete (56.2%), and the supervision carried out is good (60.9%). Based on bivariate analysis, shows that the variables related to PPSU's unsafe behavior are knowledge (p value = 0.006 and PR = 5.943), attitudes (p value = 0.017 and OR = 4.018), facilities availability (p value = 0.004 and OR = 5.400), and supervision (p value = 0.040 and OR = 3.375). Whereas the unrelated are age (p value = 1,000), years of service (p value = 0.523), and education (p value = 1,000). Keywords : Characteristics, Facilities Availability and Supervision, Unsafe Action.